2020
DOI: 10.3390/cancers12040993
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Trichoplein (TpMs) Causes Chromosome Mis-Segregation, DNA Damage and Chromosome Instability in Cancer Cells

Abstract: Mitotic perturbations frequently lead to chromosome mis-segregation that generates genome instability, thereby triggering tumor onset and/or progression. Error-free mitosis depends on fidelity-monitoring systems that ensure the temporal and spatial coordination of chromosome segregation. Recent investigations are focused on mitotic DNA damage response (DDR) and chromosome mis-segregations with the aim of developing more efficient anti-cancer therapies. We previously demonstrated that trichoplein keratin filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Mitotic abnormalities in normal cells frequently lead to missegregation of chromosomes, which produces genomic instability that triggers the development and progression of tumors ( 105 ). TNF-α and TGF-β have dual roles in causing genomic instability and mutations, as shown in Table 5 .…”
Section: Interaction Between Tnf-α and Tgf-βmentioning
confidence: 99%
“…Mitotic abnormalities in normal cells frequently lead to missegregation of chromosomes, which produces genomic instability that triggers the development and progression of tumors ( 105 ). TNF-α and TGF-β have dual roles in causing genomic instability and mutations, as shown in Table 5 .…”
Section: Interaction Between Tnf-α and Tgf-βmentioning
confidence: 99%
“…Moreover, considering that modified nuclear architecture is a marker of malignant transformation [ 32 ], we investigated whether TpMs depletion changes the genome organization of the cells through the alteration of the nuclear architecture organization, as defined by the spatial arrangement of chromosomes and other nuclear components. Altogether, we demonstrate that the telomere alterations generated in TpMs-depleted HCT116 cells are consistent with chromosome aberrations that generate chromosomal instability [ 9 ]. Our observations represent a connection between the tumor suppression ability of TpMs with its function in maintaining chromosomal segregation.…”
Section: Introductionmentioning
confidence: 74%
“…The gene encoding TpMs localizes to the chromosome 12q24.1; it was identified as Ts12q and a putative tumor suppressor at 12q [ 2 ]. Our previous investigations demonstrated that TpMs silencing causes abnormal activity of the spindle assembly checkpoint (SAC) in several cell lines [ 9 ]. SAC represents a cell cycle checkpoint during mitosis and meiosis, which allows the proper segregation of chromosomes by preventing the separation of the duplicated chromosomes during the anaphase until each chromosome is properly attached to the spindle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCHP is also involved in the spindle assembly checkpoint during cell division. TCHP knockdown leads to chromosome misalignment, DNA damage, and genomic instability, which may be an important cause of cancer development (Lauriola et al, 2020). In addition, TCHP knockdown leads to elevated expression of p16 in vascular endothelial cells, allowing the cells to reach a senescent state (Martello et al, 2020).…”
Section: Discussionmentioning
confidence: 99%